2021
DOI: 10.3390/ma14061353
|View full text |Cite
|
Sign up to set email alerts
|

The 3D-Printed Honeycomb Metamaterials Tubes with Tunable Negative Poisson’s Ratio for High-Performance Static and Dynamic Mechanical Properties

Abstract: The synthesized understanding of the mechanical properties of negative Poisson’s ratio (NPR) convex–concave honeycomb tubes (CCHTs) under quasi-static and dynamic compression loads is of great significance for their multifunctional applications in mechanical, aerospace, aircraft, and biomedical fields. In this paper, the quasi-static and dynamic compression tests of three kinds of 3D-printed NPR convex–concave honeycomb tubes are carried out. The sinusoidal honeycomb wall with equal mass is used to replace the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Hereby, an actual final Poisson's ratio improvement of 36% for PLA samples was achieved compared to the FE calculated Poisson's ratio of the reference unit cell (8). On the other hand, the final measured Poisson's ratio on TPU samples reached the same Poisson's ratio with the FE simulated unit cell (12). In addition, the possibility offered by powder bed fusion to evolve the auxetic geometry in further directions, thus creating 3D auxetic patterns, was presented demonstrating the auxeticity of ν = −0.22 in two transverse directions, i.e., in x-and y-direction.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Hereby, an actual final Poisson's ratio improvement of 36% for PLA samples was achieved compared to the FE calculated Poisson's ratio of the reference unit cell (8). On the other hand, the final measured Poisson's ratio on TPU samples reached the same Poisson's ratio with the FE simulated unit cell (12). In addition, the possibility offered by powder bed fusion to evolve the auxetic geometry in further directions, thus creating 3D auxetic patterns, was presented demonstrating the auxeticity of ν = −0.22 in two transverse directions, i.e., in x-and y-direction.…”
Section: Discussionmentioning
confidence: 68%
“…Three-dimensional printing enables easy and precise control of both the geometry and the material composition of complex shapes, which provides an opportunity to explore different geometric aspects of auxetic core structures. Research studies in this field have been performed by [12][13][14] with a variety of core materials.…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al [96] investigated the axial crushing of nylon and Al/nylon hybrid tubes and found out the crushing parameters such as EA, initial peak crush force, mean crush force, SEA, CFE, and effective crushing distance. Guo et al [97] examined the lattice reinforced thin-walled hybrid tubular structures and determined the crashworthiness parameters such as EA, mean compression force, SEA, and crush force efficiency.…”
Section: Ipcfmentioning
confidence: 99%
“…Zhang et al proposed an interesting and comprehensive review of the most recent progress in the field of additively manufactured auxetic structures and compared and summarized the results of mechanical properties under quasi-static and dynamic loading, energy absorption and numerical simulations of different geometries (Zhang et al, 2020). Moreover, it was demonstrated that by varying the internal geometric morphology of the structures, it is possible to tune their final mechanical properties, such as the elastic modulus, damage mode, peak force and energy absorption (Guo et al, 2021). Using the most recent AM techniques, it was also possible to design a single structure with a nonuniform distribution of auxetic cells, that is, a geometry with tunable PR and variable deformation properties, built by connecting different elementary cells with different PR (Han and Lu, 2018).…”
Section: Introductionmentioning
confidence: 99%